Changes in Nitrogen Use Traits Associated with Genetic Improvement for Grain Yield of Maize Hybrids Released in Different Decades. Issue 4 (1st July 2013) - Haegele, Jason W.; Cook, Kevin A.; Nichols, Devin M.; Below, Frederick E.
ABSTRACT: Further enhancement of maize ( Zea mays L.) N‐use efficiency (NUE) will benefit from a thorough understanding of how genetic improvement has shaped N use parameters. Since selection for grain yield has occurred at high N fertilizer rates, our hypothesis was that modern hybrids would have a greater response to supplemental N than hybrids from earlier eras. In 2009 and 2010, 21 single‐cross maize hybrids released between 1967 and 2006 were characterized for grain yield and N use traits. While the ability to acquire mineralized soil N did not change over era, the utilization increased with decade of introduction (0.24 kg kg –1 of plant N [kgplantN –1 ] yr –1 ; R 2 = 0.37). Increases of grain yield at high N (86 kg ha –1 yr –1 ; R 2 = 0.68) over era were accompanied by increases at low N of 56 kg ha –1 yr –1 ( R 2 = 0.69). Grain yield improvements at all levels of N were associated with decreased barrenness and increased kernel number expressed on a per‐plant and per‐area basis. Fertilizer N response, NUE, increased at a rate of 0.16 kg kg –1 of fertilizer N (kgN –1 ) yr –1 ( R 2 = 0.40). Increased NUE was positively correlated with improved N‐uptake efficiency ( r = 0.76, P ≤ 0.001), due to the greater postflowering N uptake of more recent hybrids. The response of grain yield to fertilizer N in current hybrids is more dependent on uptake of fertilizer N than the efficiency of fertilizer N utilization, and approximately two‐thirds of genetic gain for grain yield at high N can be explained by improvements in grain yield at low N.